Genetic diversity and structural analysis of 4-diphosphocytidyl-2C-methyl-D-erythritol kinase (IspE) from Plasmodium falciparum - Kavita Kadian; Sonam Vijay; Ritu Rawal; Jagbir Singh; Anup Anvikar; Veena Pande; Arun Sharma (Journal of Vector Borne Diseases, 2018)
Background & objectives: Plasmodium parasite harbours unique methylerythritol phosphate (MEP) pathway which is obligatory for the biosynthesis of isoprenoids. In malaria parasites, the isoprenoids are indispensable during hepatic, erythrocytic and gametocytic stages. Owing to the criticality of MEP pathway and the potential of its enzymes to act as antimalarial drug target, this study comprehensively investigated the genetic diversity and structural composition of 4-diphosphocytidyl-2C-methyl-D-erythritol kinase (IspE), fourth enzyme of MEP pathway in Indian Plasmodium falciparum (PfIspE). Methods: The study employed sequencing, modeling and bioinformatics approaches to examine the genetic diversity and associated structural polymorphism in the PfIspE gene amplified from the clinical blood samples collected from seven malaria endemic geographical regions of India. Results: The sequence analysis showed that PfIspE gene is highly conserved with 100% sequence identity among all the P. falciparum Indian isolates as well as with the PfIspE gene of reference strain 3D7. Phylogenetic analysis suggested that PfIspE is highly evolved and differ sufficiently from human orthologue mevalonate kinase gene. Structural modeling studies revealed that PfIspE has conserved ATP and CDPME-binding domains. The active site was observed to be relatively rigid in architecture with >60% β-pleated sheets. Interpretation & conclusion: The results of genetic, phylogeny and modeling studies strengthen the potential of PfIspE enzyme as a promising antimalarial drug target.